THE USE OF WATERPASS FOR STUDENT OF MODELLING DESIGN AND BUILDING INFORMATION (MDBI) DEPARTMENT AT SMKN 1 BANAMA TINGGANG, PANGI VILLAGE, REGENCY OF PULANG PISAU, PROVINCE OF CENTRAL KALIMANTAN - Lola Cassiophea; Vontas Alfenny Nahan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
SMKN 1 Banama Tingang is a vocational school located on 3 Padat Karya St, Pangi Village, Regency of Pulang Pisau. This school has three departments namely Welding Technology Department, Building Technology Department, and Accounting Department. Welding Technology Department is a department with the least number of students in the school which reflected the low interest in this department. One of reasons for that is due to misperception that this department is for construction worker. Another reason is due to lack of facilities for practice such as water pass. Therefore, one of solutions is to conduct the training for the use of water pass to measure land. During the training it can be seen that the interest in this department is increasing. Many questions were asked by students on how to use water pass. In the training, students were divided into several groups to match the number of water pass brought in this training. Students of PTB were actively involved to assist in the training. The training results showed that the interest of the student had increased, not only students from Building Department, but also from another departments. This indicates that the training was useful especially for the students of the school as well as PTB students involved in the training.